2018
DOI: 10.1177/1178632918791576
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Undiagnosed and Uncontrolled Hypertension in the Local Community of Byblos, Lebanon

Abstract: Objective:This study aimed to determine the prevalence and predictors of undiagnosed and uncontrolled hypertension (HTN) in a local community in Lebanon.Design and methods:In this cross-sectional study, we interviewed 911 adults in the local community of Byblos, Lebanon, and 691 were enrolled in the study. Blood pressure (BP), height, and weight were measured. The diagnosis of HTN was based on the 2013 European Society of Hypertension (ESH)/ European Society of Cardiology (ESC) guidelines (systolic BP ⩾140 mm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 26 publications
5
19
1
Order By: Relevance
“…The questionnaire is adapted from previous similar studies and the WHO STEPS wise approach guidelines on NCD risk factor surveillance questionnaire. It contains information about socio demographic characteristics, behavioral characteristics, history of chronic illnesses, hypertension related knowledge questions and weight, height and blood pressure measurements [ 6 , 13 , 20 – 30 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire is adapted from previous similar studies and the WHO STEPS wise approach guidelines on NCD risk factor surveillance questionnaire. It contains information about socio demographic characteristics, behavioral characteristics, history of chronic illnesses, hypertension related knowledge questions and weight, height and blood pressure measurements [ 6 , 13 , 20 – 30 ]…”
Section: Methodsmentioning
confidence: 99%
“…Different studies conducted in different areas revealed that younger and older age, lower socioeconomic status, drinking alcohol, being underweight, absence of associated cardiovascular co-morbidities, no familial history of hypertension and primary educated individuals are more likely to have undiagnosed hypertension [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…15 In Byblos, Lebanon, 42.7% of study participants had undiagnosed or uncontrolled HTN. 16 The prevalence of undiagnosed HTN in a rural community in Sudan was 38.2% (36.7% among males and 39.3% among females). 17 In Dabat, northern Ethiopia, only 16.4% of patients with HTN were on antihypertensive treatment, while 83.4% had not been diagnosed and/or treated for HTN.…”
Section: Introductionmentioning
confidence: 94%
“…16 The prevalence of undiagnosed HTN in a rural community in Sudan was 38.2% (36.7% among males and 39.3% among females). 17 In Dabat, northern Ethiopia, only 16.4% of patients with HTN were on antihypertensive treatment, while 83.4% had not been diagnosed and/or treated for HTN. 18 The prevalence of undiagnosed HTN was 13.3% in Gulele Sub-city, Addis Ababa, Ethiopia.…”
Section: Introductionmentioning
confidence: 94%
“…Marshallese with T2DM had a high prevalence of diagnosed hypertension or undiagnosed high blood pressure (62.9%), more than three times the prevalence of hypertension (19.2%) recorded in the only prior study reporting hypertension (�140/90) among Marshallese with T2DM [17]. Among those with blood pressure readings indicative of hypertension, prevalence of undiagnosed high blood pressure was found to be 38.5% among Marshallese with T2DM, which is higher than the undiagnosed hypertension (�140/90) documented in other populations [9,[29][30][31][32].…”
Section: Discussionmentioning
confidence: 70%